Bed-Stretcher for Burial Process of COVID-19 Corpse: A Preliminary Design and Strength Analysis - Charline Tiara Rehuellah Pingak; Maria Anggi Octaviani; Given Chris Yuenan; Farid Triawan (ASEAN Journal of Science and Engineering, 2022)
The number of COVID-19 corpses is highly increased since 2020. This situation tends to risk the health workers directly interacting with COVID-19 victims during the burial process. In Indonesia, the conventional method of burial process requires four to eight health workers. Thus, minimizing the number of involved health workers is needed. This paper aims to propose a bed-stretcher that assists the burial process of the COVID-19 corpses efficiently. Hence, the number of people involved can be minimized. The design considers a maximum weight of 2000 N of the coffin, which includes the corpse inside. The device is equipped with a shaft-pulley system, gear, and ratchet mechanism to lower the coffin inside the grave. The strength analysis of the shaft-pulley system by theoretical approach is conducted under static and fatigue loading conditions to estimate the service life. As a result, the calculated safety factor demonstrates a value of more than one, indicating the structure is safe under both static and fatigue loading conditions. Moreover, the device can be operated only by two health workers. In addition, this work is expected to contribute to the innovative idea of engineering products to overcome the Pandemic of COVID-19.